Interação de bebês com livros literários - Pinto, Marcela Lais Allgayer (My University, 2018)
The present study aims to analyze the interaction of infants with literary books in order to contribute to the processes of literary education in Early Childhood Education. The dissertation is based on investigative research through the application of reading mediation situations with a group of infants. For that, specific environments were prepared and that allowed the interaction of the small readers and, in a playful way, four books were presented, focused on the interests and needs of the children. The research is justified because it is not always given the necessary attention to the literary book, which contributes to the insertion of this age group into the literate world. The exploratory qualitative research resulted in the planning, application, description and analysis of literary interventions from books selected by the National Library in the School Program of 2014. Reading possibilities were identified in the literary works, based on interests and needs expressed in childish doing. The study reflected on different modes of infant interaction with children'sliterature, the space, nature and other subjects, contemplating the dialogue between the universe of books and the reality of children, so construct new meanings. Thus, the importance of adequate space for the baby / reader during reading mediation situations is highlighted, which favored the expansion of the children's ability to understand and express themselves through diversified experiences, among them the conversation, the music and the listening of stories. Still, the research provided the opportunity for the small ones to appropriate the different forms of reading, which allows them to expand their cognitive capacity, expressiveness and to be able to "read" the reality in which they are inserted.
O presente estudo tem como objetivo analisar a interação de bebês com livros literários, a fim de contribuir para os processos de educação literária na Educação Infantil. A dissertação fundamenta-se em pesquisa investigativa por meio de aplicação de situações de mediação de leitura com grupo de bebês. Para tanto, foram preparados ambientes específicos e que permitiram a interação dos pequenos leitores e, de forma lúdica, foram apresentados quatro livros, voltados aos interesses e necessidades das crianças. O estudo justifica-se pelo fato de nem sempre ser dada a atenção necessária ao livro literário, que contribui para a inserção desta faixa etária ao mundo letrado. A pesquisa qualitativa, de natureza exploratória, resultou no planejamento, aplicação, descrição e análise de intervenções literárias a partir de livros selecionados pelo Programa Nacional Biblioteca na Escola de 2014. Foram apontadas possibilidades de leitura presentes nas obras, a partir dos interesses e das necessidades expressas no fazer infantil. A investigação refletiu acerca de diferentes modos de interação de bebês com a literatura infantil, com o meio, com a natureza e com os outros sujeitos, contemplando o diálogo entre o universo dos livros e a realidade das crianças, de modo a construírem novos sentidos. Assim, destaca-se a importância do espaço adequado ao bebê/leitor durante as situações de mediação de leitura, as quais favoreceram a ampliação da capacidade de compreensão, expressão, por meio de experiências diversificadas, entre elas a conversa, a música e a escuta de histórias. Ainda, a pesquisa proporcionou a oportunidade dos pequenos se apropriarem das diversas formas de leitura, o que possibilita a ampliação de sua capacidade cognitiva, de expressividade e de serem capazes de “ler” a realidade na qual estão inseridos
Keywords: Educação; Educação de crianças; Incentivo à leitura - Crianças; Literatura infantil; Education; Education of children; Reading promotion - children; Children's literature